Polyhedral Dialogues: OPAVIVARÁ! and the Intersection of Art, Society and Urban Space - Campos, Lívia Fernandes; Grando, Angela (Farol, 2024)
This article analyzes the work of the Rio de Janeiro art collective OPAVIVARÁ!, highlighting its contribution to contemporary art through interventions in public spaces and cultural institutions since 2005. The collective is known for its interactive actions that encourage the participation of diverse groups, promoting the occupation of local spaces and exploring experimental forms of socialization. Using relational devices created by the group, its projects connect ideas, practices, ways of life and objects, proposing new forms of cultural exchange. The works bear the collective’s signature, without mentioning individual names, emphasizing collectivity as its artistic identity and reinforcing the intersections between art, public space and politics.